Use of cancer data for cancer control in the Eastern Mediterranean Region: Results of a survey among population‐based cancer registries. Issue 3 (13th August 2020) - Znaor, Ariana; Fouad, Heba; Majnoni d'Intignano, Fosca; Hammerich, Asmus; Slama, Slim; Pourghazian, Nasim; Eser, Sultan; Piñeros Petersen, Marion; Bray, Freddie
Abstract: Data from population‐based cancer registries (PBCR) are critical for planning, monitoring and evaluation of cancer control programs, but are frequently underutilized by key stakeholders. As part of the ongoing partnership of the International Agency for Research on Cancer (IARC) and the WHO Eastern Mediterranean Regional Office (EMRO) in cancer surveillance, we designed a cancer registry survey to assess the level of involvement of PBCR in national cancer control planning across the region. A questionnaire on registry characteristics, their contribution to cancer control and perceived barriers, was sent to 14 countries with operational PBCR. We obtained replies from Bahrain, Egypt, Iraq, Iran, Jordan, Kuwait, Lebanon, Morocco, Oman, Qatar, Saudi Arabia, Tunisia and the United Arab Emirates. We found a high participation of PBCR in cancer control planning (all registries involved, 46% routinely) and the evaluation of screening (92% registries involved, 46% routinely), but a much lower level of participation in palliative care and rehabilitation activities. Specified barriers included poor governance, a lack of awareness by policy makers, insufficient resources and a limited availability of data electronically, including mortality data. Appropriate planning to ensure the sustainability of PBCR (including the employment of permanent staff), increasing training, building research capacity and ensuring an efficient provision of high‐quality data to policymakers, were among the proposed solutions. The results of our study reinforce the need for further tailoring of activities in support of cancer registration and enhanced networking among stakeholders, toward improving quality and use of cancer registry data for cancer control in the EMR. Abstract : What's new? Data from population‐based cancer registries are critical for the planning, monitoring, and evaluation of cancer control programs. While the coverage of population‐based cancer registries has increased in the Eastern Mediterranean Region, the extent to which the data are presently used for national cancer control purposes remains unclear. This survey of population‐based cancer registries reveals their high participation in cancer control planning and in the evaluation of screening, but a much lower level of participation in planning and evaluation of palliative care and rehabilitation activities. Registry respondents also perceived a disconnection from stakeholders and a need for greater visibility of the collected and analysed data.